MASTITIS IN CULLED FEMALE CAMELS IN THE SUDAN - A.M, Abeer; Y.A, Sabiel; M. T. , Musa; A. M, Zakia (Journal of Veterinary Medicine and Animal Production, 2021)
Bacterial causes of mastitis in female camels were investigated. A total of 660 she- camels were examined for clinical mastitis. The camels examined were Butana, Arabic, Kassala, Rashaidi, Anafi and Kennana ecotypes. Thirty one milk samples and 165 tissues specimens affected udders were collected from animals of different age groups at Tumbool slaughter house, Al-gazera State, Sudan. All milk samples were positive for California Mastitis Test. A highest prevalence of 77.8% clinical mastitis was found in the Rashaidi ecotype and the lowest of 25.5% was found in western Arab and Al Gadarif ecotypes. A high prevalence was also observed in camels Over 14 years. One hundred and fourteen bacteria isolated from the udder ية tissues and identified by conventional bacteriological tests and by the rapid test (Himedia strips system). Forty of the isolates (35.8%) were Staphylococcus spp. followed by 29(25.4%) Streptococcus spp and Micrococcus spp24(21%). Other bacteria recovered were Bacillus cereus, Acinetobacter spp. Mannhaemia haemolytica and Klebsiella pneumonia, each represented one isolate (0.9%).